Using the somatic cell count report - Dunham, James R. (Kansas Agricultural Experiment Station, 2011)
High-producing dairy herds can consistently average a somatic cell count (SCC) <200,000. Herds with consistently higher averages can decrease SCC and realize higher profits. The SCC report discloses the pitfalls that need to be addressed before improvement can be made.
Keywords: Somatic cell count